Ensemble of logistic maps with genetic algorithm for optimal pixel selection in image steganography - Chandrasekaran, Jeyamala; Arumugam, Girija; Rajkumar, Deepthi (2015 2nd International Conference on Electronics and Communication Systems (ICECS), 2015)
Due to the explosive growth of internet technologies and its applications, steganography and steganalysis have become an prominent area of research. Least Significant Bit (LSB) substitution, a spatial domain steganographic technique involves replacement of the least significant bit of randomly selected pixels in the cover image with the secret message bit. The distortion in the cover image increases with the increasein size of the information to be hidden. The research focus of the problem is to optimize the pay load capacity subject to minimal visual degradation. The problem solution is to employ logistic maps for the random selection of pixels. The randomness of the pixels selected is further optimized by the application of genetic algorithm subjected to the minimal distortion of the cover image. Experimental results prove the robustness of the proposed algorithm in terms of improved payload capacity, minimal degradation in picture quality, high randomness in pixel selection and high security compliance.